INTERNALISASI NILAI-NILAI ANTIKORUPSI MELALUI PENDIDIKAN KARAKTER DALAM MEMBENTUK INTEGRITAS PESERTA DIDIK: STUDI KASUS DI SMA NEGERI 1 TAKENGON - Andi Yacub; Cut Khairani; Najmuddin Najmuddin; Muhammad Iqbal (CV. Bunda Ratu, 2026)
Corruption remains a persistent challenge that undermines integrity within educational environments, highlighting the need for character-based anti-corruption education from an early stage. This study aims to analyze the internalization of anti-corruption values through character education in shaping students' integrity at SMA Negeri 1 Takengon. The findings indicate that the internalization process extends beyond classroom instruction and develops through the interaction of learning activities, school culture, teacher role modelling, institutional governance, students' social experiences, and family support. The values of honesty, justice, responsibility, simplicity, and courage are strengthened through continuous habituation, collaborative learning, decision-making opportunities, and the consistent implementation of school norms. These interconnected experiences transform anti-corruption values from conceptual understanding into everyday practices reflected in students' attitudes and behaviors. The study further demonstrates that effective anti-corruption character education requires an educational ecosystem in which pedagogical practices, organizational culture, and stakeholder collaboration reinforce one another. This perspective contributes to the development of anti-corruption character education by emphasizing that integrity is cultivated through sustained educational experiences rather than through the transmission of moral knowledge alone.